Contrôle De L’inflation En Regime De Change Fixe: Le Cas De La Communaute Economique Et Monetaire d’Afrique Centrale (CEMAC) - Robert, Tangakou Soh; ArsѐneMba Fokwa; Johnson, Akanga Reuben (European Scientific Journal, ESJ, 2017)
This paper focuses on the determinants of inflation under different policy rules and fixed exchange rate regime, the example of the CEMAC zone. The purpose of this paper is to check the behaviour of inflation in fixed exchange rate regime for a flexible targeting period and a period of strict targeting. The data used are mainly from the World Bank, in «the book of world development indicators» contained in the CD -ROM (WDI 2015). Working for the periods 1977-1994, 1995-2012 and 1977-2012, the analyses was done with a dynamic panel that has the distinction of being among the independent variables, the endogenous variable lagged one or more periods. The endogenous variable is the rate of inflation. Estimates made from the Arellano and Bond (1991) method, it is clear that during the period (1977- 1994) of flexible inflation targeting, money supply, trade balance and the exchange rate are the main determinants of inflation. During the period (1995-2012) of strategy of strict inflation targeting, the main determinants of inflation are the benefits of natural resources, the trade balance and the economic crisis. The determinants of inflation have opposing effects of a match type to another and it is the combination of these effects for each variable that shows the different effects of the determinants of inflation over the period. The exchange rate increased the rate of inflation over the first sub-period (1977-1994) and throughout the entire period (1977-2012). In times (1995-2012) of strict inflation targeting, these negative effects were mitigated at the expense of economic growth. Countries with fixed exchange rate regime should not adopt a strict policy of inflation targeting, but should alternate with the growth objective by facilitating financing for investments.